2009
DOI: 10.1017/s1368980008002395
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient deficiency status among women of desert areas of western Rajasthan, India

Abstract: Objective: To assess the magnitude of three micronutrient deficiency disorders (iron, vitamin A and iodine), nutritional deficiencies and their association with related factors. Material and Methods: Using the three-stage sampling technique, a study was conducted in twenty-eight villages of Jodhpur district. A total of 1193 women, 384 pregnant, 400 lactating and 409 non-pregnant non-lactating controls (15 years and above, women who have not attained their family status) were examined for three micronutrient de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 6 publications
3
33
0
Order By: Relevance
“…The MUIC of women at the first and second visits was 106 and 71 lg/L, respectively, below the 150 lg/L cutoff, indicating iodine deficiency (2); UIC decreased by 2% for every week of gestation. IDD in pregnant Indian rural women was observed recently in two cross-sectional studies from the Indian state of Rajasthan, which reported an MUIC of 127 lg/L in pregnant women at any stage of gestation and 118 lg/L in pregnant women of > 28 weeks of gestation (7,8).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The MUIC of women at the first and second visits was 106 and 71 lg/L, respectively, below the 150 lg/L cutoff, indicating iodine deficiency (2); UIC decreased by 2% for every week of gestation. IDD in pregnant Indian rural women was observed recently in two cross-sectional studies from the Indian state of Rajasthan, which reported an MUIC of 127 lg/L in pregnant women at any stage of gestation and 118 lg/L in pregnant women of > 28 weeks of gestation (7,8).…”
Section: Discussionmentioning
confidence: 94%
“…Thus, it is not surprising that IDD has been reported in rural Indian pregnant women in these areas (7,8). However, there is little information on the iodine status of tribal Indian pregnant women as tribal areas are typically more deprived than rural parts of India.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al, 2009, reported low level of MUI levels (117.5 μg/L) among pregnant women from 28 villages of Jodhpur, Rajasthan. Further, a high proportion of women (80.8 %) were consuming salt, having inadequate iodine content [13]. A study among tribal women from Nagpur, Maharashtra, reported MUI levels of 106 and 71 µg/L in the second and third trimester of pregnancy, respectively [14].…”
Section: Discussionmentioning
confidence: 95%
“…Another study in 151 rural adolescent pregnant mothers belonging to low socioeconomic status (SES) from Uttaranchal, reported MUI as 95 μg/L; with a goiter rate of 14.6% [12]. Singh et al, 2009, reported low level of MUI levels (117.5 μg/L) among pregnant women from 28 villages of Jodhpur, Rajasthan. Further, a high proportion of women (80.8 %) were consuming salt, having inadequate iodine content [13].…”
Section: Discussionmentioning
confidence: 99%
“…A prevalence of 30-50% was reported among the women of reproductive age by several authors, 14,15,[19][20][21][22][23][24][25][26][27][28][29][30] in their studies conducted in various parts of the world.…”
Section: Discussionmentioning
confidence: 99%